Root-soil-phosphate interactions in rice growing in aerobic soil : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Soil Science at Massey University - Trolove, Stephen Neil (Massey University, 2000)
Rice (Oryza sativa L.) is the staple food of subsistence farmers in the vast areas of Ultisols and Oxisols of the tropical and subtropical rainfed uplands and lowlands Phosphorus (P) deficiency and soil acidity commonly constrain yields. Phosphorus fertiliser is considered an expensive input, and must therefore be used efficiently. The objective of this thesis was to investigate fertiliser strategies and plant mechanisms that could enhance the uptake efficiency of P by aerobically grown rice. The long-term aim of understanding rice P-uptake mechanisms is that such research will help in developing P-efficient rice varieties. In acid soils, aluminium (Al) toxicity restricts root growth and therefore limits P uptake. A bioassay was developed as a basis to compare two techniques for assessing concentrations of phytotoxic Al. It was found that Al in soil solution extracted by centrifugation correlated better with rice root extension than Al extracted in 0.02 M CaCl2. Aluminium toxicity was found not to restrict root growth (hence P uptake) in the Philippines Ultisol (Cavinti soil) used in later experiments. Experiments investigating the effect of different fertiliser management practices, showed that banding of fertiliser P, as opposed to incorporating P fertiliser throughout the soil, enhanced the availability of P to rice grown in the high P-fixing Cavinti soil. The practice of applying green manure with reactive phosphate rock (RPR) decreased the dissolution of RPR because mineralisation of green manure nitrogen increased the soil pH. Aerobically grown rice exhibited a number of mechanisms that would enhance P uptake; rhizosphere acidification, localised proliferation of fine roots in P-rich zones, and association with mycorrhizae. Mathematical modelling indicated that upland rice must be able to release solubilising agents, e.g. organic anions, in order to explain the observed P uptake in banded, moderately fertilised soil. By extracting soil fertilised at different P rates with citrate solutions, it was found that more P was extracted, per mole of citrate added, from highly fertilised soil. This indicated that there would be a positive interaction between banding fertiliser P and solubilisation by organic anions. Initial extraction, storage and detection methods were unable to identify significant quantities of organic acids in the rhizosphere of aerobically grown rice. Better methods for extracting organic anions from soil were developed, and improved procedures for studying the mechanisms of plant induced changes in the rhizosphere are proposed.
Keywords: Rice growing; Phosphatic fertilisers